2020
DOI: 10.1002/1878-0261.12667
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Hippo coactivator YAP1 through BET bromodomain inhibition in esophageal adenocarcinoma

Abstract: Hippo/YAP1 signaling is a major regulator of organ size, cancer stemness, and aggressive phenotype. Thus, targeting YAP1 may provide a novel therapeutic strategy for tumors with high YAP1 expression in esophageal cancer (EC). Chromatin immunoprecipitation (ChiP) and quantitative ChiP-PCR were used to determine the regulation of the chromatin remodeling protein bromodomain-containing protein 4 (BRD4) on YAP1. The role of the bromodomain and extraterminal motif (BET) inhibitor JQ1, an established BRD4 inhibitor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…The tumorigenic effect of YAP1 has been verified in recent studies [15]. Therapeutic opportunities targeting the YAP1/ TEAD-dependent transcription are being tested in different neoplasms [16].…”
Section: Discussionmentioning
confidence: 91%
“…The tumorigenic effect of YAP1 has been verified in recent studies [15]. Therapeutic opportunities targeting the YAP1/ TEAD-dependent transcription are being tested in different neoplasms [16].…”
Section: Discussionmentioning
confidence: 91%
“…Once YAP1 and TAZ are released, MST1/2 and LATS1/2 become deactivated, YAP1 and TAZ are dephosphorylated, and then they translocate into the nucleus to bind to TEADs to promote tumor development. [ 12 , 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Hippo coactivator YAP1 mediates EGFR overexpression and confers chemoresistance in EC [ 37 ]. Targeting the Hippo coactivator YAP1 through BET bromodomain inhibition could suppress EC growth [ 38 ]. Of note, various studies had indicated that TGF- β signaling was cross talked with these signalings in human cancers.…”
Section: Discussionmentioning
confidence: 99%